Perilaku Berwiruasaha UKM Di Kabupaten Sumba Timur (Studi Komperasi Multi Etnis) - Tumpal Pangihutan Situmorang; Norlina Rambu Jola Kalunga (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2016)
The problems and obstacles faced by micro enterpreneurs in Indonesia are generally same, the things that make existence of the UKM is different because the aspect of enterpreneurship behaviour, natural resources potential as well as culture which is related to the behaviour and geodemography which is related to culture, simi where they start liarity, and difference of cultural values, history, and belief systemas and its environment. The rising of ethinic diversity in one country because this country welcome and accept different ethinicity to start their bussiness and to develop, expand and contribute to local communities. This research focuses on the behaviour of enterpreneurship of certan ethinicity that make this certain ethnic have a high spirit of enterpreneurship but other ethnic has low spirit of enterpreneurship.The variable of this research is the characteristic of enterpreneurship, that is, self-confidence, job-oriented, result oriented, risk taker, leadership, originality, future orientation. The comparison study involved ethnics east ans west Sumbanese, javanese, bimarese, sabunese, bugis,. The sample used is systematic sampling dan purposive sampling.The result show that the behaviour of enterpreuners of each ethnics is different from each other in term of hard-work, risk takers, responsible, future oriented which value the achievement higher than money.Key words: Micro enterpreneur, small and average, bussiness enterpreneur, ethnic